Rough Convergence for Generalized Difference Sequences by a Compact Operator in Probabilistic \(n\)-Normed Spaces - Kaur, Manpreet; Chawla, Meenakshi (Communications in Mathematics and Applications, 2024)
Using compact operator in probabilistic \(n\)-normed spaces, we develop and investigate the notion of rough convergence for  generalized difference sequences. In relation to rough convergence in probabilistic \(n\)-normed spaces, certain fundamental conclusions regarding the concept of rough limit points for a difference sequence are defined.
Keywords: Rough convergence; Rough limit points; Probabilistic n-normed space; Compact linear operator